Glyphosate and a glyphosate-based herbicide dysregulate the epigenetic landscape of Homeobox A10 (Hoxa10) gene during the endometrial receptivity in Wistar rats - Lorenz, Virginia; Doná, Florencia; Cadaviz, Dalma B.; Milesi, María M.; Varayoud, Jorgelina (Frontiers in Toxicology, 2024)
We observed that gestational plus lactational exposure to glyphosate (Gly), as active ingredient, or a glyphosate-based herbicide (GBH) lead to preimplantation losses in F1 female Wistar rats. Here, we investigated whether GBH and/or Gly exposure could impair Hoxa10 gene transcription by inducing epigenetic changes during the receptive stage in rats, as a possible herbicide mechanism implicated in implantation failures. F0 dams were treated with Gly or a GBH through a food dose of 2 mg Gly/kg bw/day from gestational day (GD) 9 up to lactational day 21. F1 female rats were bred, and uterine tissues were analyzed on GD5 (preimplantation period). Transcripts levels of Hoxa10, DNA methyltransferases (Dnmt1, Dnmt3a and Dnmt3b), histone deacetylases (Hdac-1 and Hdac-3) and histone methyltransferase (EZH2) were assessed by quantitative polymerase chain reaction (qPCR). Four CpG islands containing sites targeted by BstUI methylation-sensitive restriction enzyme and predicted transcription factors (TFs) were identified in Hoxa10 gene. qPCR-based methods were used to evaluate DNA methylation and histone post-translational modifications (hPTMs) in four regulatory regions (RRs) along the gene by performing methylation-sensitive restriction enzymes and chromatin immunoprecipitation assays, respectively. GBH and Gly downregulated Hoxa10 mRNA. GBH and Gly increased DNA methylation levels and Gly also induced higher levels than GBH in all the RRs analyzed. Both GBH and Gly enriched histone H3 and H4 acetylation in most of the RRs. While GBH caused higher H3 acetylation, Gly caused higher H4 acetylation in all RRs. Finally, GBH and Gly enhanced histone H3 lysine 27 trimethylation (H3K27me3) marker at 3 out of 4 RRs studied which was correlated with increased EZH2 levels. In conclusion, exposure to GBH and Gly during both gestational plus lactational phases induces epigenetic modifications in regulatory regions of uterine Hoxa10 gene. We show for the first time that Gly and a GBH cause comparable gene expression and epigenetic changes. Our results might contribute to delineate the mechanisms involved in the implantation failures previously reported. Finally, we propose that epigenetic information might be a valuable tool for risk assessment in the near future, although more research is needed to establish a cause-effect relationship.